Phylogeography and Population Genetics of the Moor frog (Rana arvalis Nilsson) in Northern Europe - Knopp, Theresa (Helsingin yliopisto, 2010)
The ongoing climate change along with increasing levels of pollutants, diseases, habitat loss and fragmentation constitute global threats to the persistence of many populations, species and ecosystems. However, for the long-term persistence of local populations, one of the biggest threats is the intrinsic loss of genetic variation. In order to adapt to changes in the environment, organisms must have a sufficient supply of heritable variation in traits important for their fitness. With a loss of genetic variation, the risk of extinction will increase. For conservational practices, one should therefore understand the processes that shape the genetic population structure and also the broader (historical) phylogenetic patterning of the species in focus. In this thesis, microsatellite markers were applied to study genetic diversity and population differentiation of the protected moor frog (Rana arvalis) in Fennoscandia from both historical (evolutionary) and applied (conservation) perspectives. The results demonstrate that R. arvalis populations are highly structured over rather short geographic distances. Moreover, the results suggest that R. arvalis recolonized Fennoscandia from two directions after the last ice age. This has had implications for the genetic structuring and population differentiation, especially in the northernmost parts where the two lineages have met. Compared to more southern populations, the genetic variation decreases and the interpopulation differentiation increases dramatically towards north. This could be an outcome of serial population bottlenecking along the recolonization route. Also, current isolation and small population sizes increase the effect of drift, thus reinforcing the observed pattern. The same pattern can also be seen in island populations. However, though R. arvalis on the island of Gotland has lost most of its neutral genetic variability, our results indicate that the levels of additive genetic variation have remained high. This conforms to the conjecture that though ...